Lean manufacturing practices for operational and business performance : A PLS-SEM modeling analysis - Shrikant, Panigrahi; Khaloud Khalfan, Al Ghafri; Wafa Rashid, Al Alyani; Muhammad Waris, Ali Khan; Tauﬁq, Al Madhagy; Asadullah, Khan (InTech, 2023)
The main objective of the study is to empirically investigate the influence of lean manufacturing (LM) practices on the operational and business performance of manufacturing companies in Oman. Methods: Empirical data on LM practices and performance were collected using a self-administered structured survey questionnaire and the sampling frame was manufacturing companies in Oman. In total 300 questionnaires were distributed among 185 companies and a total of 107 with a response rate of 35.6 percent. Findings: The statistical analysis obtained from structural equation modeling found that lean manufacturing practices can explain operational performance, however, were unable to benefit overall business performance. Out of eight LM practices considered, small-lot production and quick setups were found to be the most adopted practices in manufacturing companies. Novelty: Even though LM has become a fundamental aspect of industrial manufacturing processes; little is known about its impact on performance. This study adds value to the literature by examining the key LM practices-performance relationships within the manufacturing companies in Oman. These findings have significant implications for improving manufacturing organizations' operational and business performance through lean manufacturing strategies.